PENERAPAN METODE BOARD RUSH DALAM MENINGKATKAN KEAKTIFAN BELAJAR SISWA - Ari Maulana Ibrahim; Nurhalimah; Siti Sarah Susanti; Rifanny Dwi Putri; Dwi Nurmahabbah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students’ learning activeness through the implementation of the Board Rush method in class XI of MA Yasti Cisaat, Sukabumi Regency. The research employed a Classroom Action Research (CAR) design using a mixed-methods approach, conducted in several cycles consisting of planning, action, observation, and reflection stages. The participants of this study were 30 students. Data were collected through observation, documentation, and field notes. Qualitative data were used to describe the learning process and students’ responses to the implementation of the Board Rush method, while quantitative data were utilized to measure the improvement of students’ learning activeness based on indicators such as active participation, attention, willingness to ask questions, ability to answer, and engagement in the learning process. The findings indicate that the implementation of the Board Rush method significantly and progressively enhances students’ learning activeness in each cycle. Therefore, the Board Rush method is proven to be an effective alternative teaching strategy to promote students’ active involvement in the learning process.